Clinicopathilogical Correlation of Nephrotic Syndrome in a Tertiary Care Hospital - Mohajan, Monisha; Biswas, Parijat; Saha, Emon Kalyen; Dutta, Pradip Kumar (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Nephrotic Syndrome (NS) in adult is diagnosed by renal biopsy. 50% of causes are secondary. Clinical features may or may not correlate with the histopathological features. For this, renal histopathology is important. The aim of our study is to find out the clinical features and its correlation with histopathological types of nephrotic syndrome in our context. Materials and methods: Study was conducted among 50 patients of nephrotic syndrome admitted in the Department of Nephrology CMCH. Data was collected in a structured case record form, renal biopsy was done . Investigations was done in the Department of pathology of CMCH. Data was analyzed by SPSS-20. Results: Among 50 cases, male to female ratio was 1.2:1. Regarding renal biopsy findings Membranous Nephropathy (MN) Focal Segmental Glomerulosclerosis (FSGS) Membranoproliferative Glomerulonephritis (MPGN) Focal Segmental Glomerulonephritis (FSGN) Diffuse Proliferative Glomerulonephritis (DPGN) and Lupus Nephritis (LN) was found in 10,2,22,12,2,2 cases respectively. Generalised oedema, pleural effusion, ascites, hypertension (Blood pressure >140/90) were present in 46,35,43,18 cases respectively. Microscopically, hematuria, proteinuria (>8gm/day), severe hypercholesterolaemia (>400mg/day), severe hypoalbuminaemia (<2.5mg/day) renal failure were found in 16,10,16,44,22 caese respectively. Conclusion: The study partially gave a snap shot of clinical features of patients correlating with corresponding histopathological features. Knowledge deducting from NS correlation will help us to initiate treatment and later on referral to tertiary center when patient is found with clinical features of NS in a remote place where renal biopsy is not available. JCMCTA 2023 ; 34 (1) : 52-56